2015
DOI: 10.1002/2015gl065161
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous carbon uptake in Australia as seen by GOSAT

Abstract: One of the unanswered questions of climate change is how the biospheric uptake of carbon responds to events such as droughts and floods. Especially, semiarid regions have received interest recently, as they can respond very rapidly to changing environmental conditions. Here we report on a large enhanced carbon sink over Australia from the end of 2010 to early 2012 detected using the Greenhouse Gases Observing SATellite (GOSAT). This enhanced sink coincides with the strong La Niña episode, accompanied by record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
4
46
0
1
Order By: Relevance
“…The magnitude of the 2010–11 enhanced land carbon sink as derived from GOSAT inversion in this study, if reported based on calendar year, was 0.77 Pg in 2011, which is very similar with 0.79 Pg C reported by Poulter et al 8. or 0.86 Pg C from another recent study37.…”
Section: Resultssupporting
confidence: 91%
“…The magnitude of the 2010–11 enhanced land carbon sink as derived from GOSAT inversion in this study, if reported based on calendar year, was 0.77 Pg in 2011, which is very similar with 0.79 Pg C reported by Poulter et al 8. or 0.86 Pg C from another recent study37.…”
Section: Resultssupporting
confidence: 91%
“…6a), which is largely due to the contribution from Australia as consistent with the indication by previous works (Poulter et al 2014;Detmers et al 2015) (Fig. 6d).…”
Section: Discussionsupporting
confidence: 81%
“…The X CO 2 derived from GOSAT has an accuracy on the order of a few tens of a percent (Butz et al, 2011;Guerlet et al, 2013b;Buchwitz et al, 2017a). X CO 2 retrievals with this level of accuracy can provide valuable information on the variation of CO 2 (Rayner and O'Brien, 2001;Houweling et al, 2004;Guerlet et al, 2013a;Basu et al, 2014;Detmers et al, 2015). In July 2014, NASA's Orbiting Carbon Observatory-2 (OCO-2) satellite was successfully launched.…”
Section: Introductionmentioning
confidence: 99%